2023
DOI: 10.25236/fer.2023.061411
|View full text |Cite
|
Sign up to set email alerts
|

Application of Production-Oriented Approach (POA) in College English Teaching in Normal Universities

Abstract: Production-oriented Approach (POA), a teaching method in English language teaching, adopts practical language usage scenarios, pays attention to students' language output, promotes students to master the English language and its culture through practice, and improves their language application abilities. This article took college English teaching in normal universities as the background and explored the application of POA in English language teaching, aiming to improve students' grades and English communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
0
1
Order By: Relevance
“…The findings of the study provided intriguing insights into Chinese university students' English writing and speaking proficiency under varied instructional approaches. Generally, students instructed through the POA demonstrated enhanced English writing and speaking proficiency, aligning with previous research findings (Ding, 2023;Zhang, 2020b). Specifically, the observed increase in writing and speaking fluency, as reflected in ANWT, NP and NR, in the EG is consistent with the positive impact of the POA reported in prior studies (Li, 2018;Liu et al, 2020), though they used different indicators (e.g., human ratings of tests) to quantify the variables.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings of the study provided intriguing insights into Chinese university students' English writing and speaking proficiency under varied instructional approaches. Generally, students instructed through the POA demonstrated enhanced English writing and speaking proficiency, aligning with previous research findings (Ding, 2023;Zhang, 2020b). Specifically, the observed increase in writing and speaking fluency, as reflected in ANWT, NP and NR, in the EG is consistent with the positive impact of the POA reported in prior studies (Li, 2018;Liu et al, 2020), though they used different indicators (e.g., human ratings of tests) to quantify the variables.…”
Section: Discussionsupporting
confidence: 88%
“…However, the non-significant improvement in complexity and accuracy, both in English writing and speaking, in the POA tends to contrast previous findings in literature that suggests that this approach could facilitate comprehensive development of English communication Liu et al, 2020), but somehow reflects the concern in Ding's (2023) qualitative research that stakeholders (e.g., students) might not consider the POA as effective as anticipated. This concern is particularly evident when compared with the CG's higher D-score at the end of the study, and its immediate improvement of writing accuracy indicated by PET and speaking complexity on the dimensions of grammar and vocabulary indicated by MLAS, RS and D-score throughout the study, which is a well-established finding in relevant literature (Du, 2021).…”
Section: Discussioncontrasting
confidence: 74%